(untitled) (Raparin Journal of Humanities (RJH), 2022)
This thesis entitled “Religious Ceremonies and Beliefs in Ancient Iran’s History before the emergence of Zoroastrianism” is an attempt to present and explain the history of the emergence of religious beliefs in ancient Iran from stone ages to the 7th century BC such as the Elamites as one of the tribes of Zagros Mountains who became the first inhabitants of Iran. Also, the Medes were one of the Indo-European tribes that moved to Iran and dwelt there. Through researching about the ways of their lives, types of their worships, and the burial of their deaths we will get some religious beliefs.